LENGTH AND LETTER COMBINATION. VOCABULARY OF FIRST DECLENSION NOUNS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
These are combinations of letters that create specific consonant sounds in words. Examples of common consonant letter combinations include “ch,” “sh,” “th,” “ph,” “st,” “tr,” and many more. These combinations often have unique sounds and can be found at the beginning, middle, or end of words. Is there a specific aspect or question about consonant letter combination.